Evaluating fire-induced structural degradation of RCC buildings: NDT-based evidence from Nepalese case studies - Ojha, Bimal; Khatri, Abhinesh; Jha, Gajendra Kumar; Parajuli, Hari Ram (Journal of Innovations in Engineering Education, 2026)
Fire incidents pose a serious threat to the structural integrity of reinforced cement concrete (RCC) buildings, particularly when exposure is localized and prolonged. Recently, several RCC buildings in Nepal have been affected by deliberate fire incidents, highlighting the need for systematic post-fire structural assessment. This study evaluates fire-induced structural degradation of RCC buildings through a comprehensive literature review and Non-Destructive Testing (NDT)-based investigation of selected Nepalese case studies. The literature review outlines key thermo-mechanical degradation mechanisms in concrete at elevated temperatures, including strength loss, cracking, spalling, and bond deterioration, and discusses limitations of standard fire exposure models in representing real fire scenarios. Field investigations were conducted using rebound hammer and ultrasonic pulse velocity (UPV) tests to assess residual concrete quality in fire-affected beams, columns, slabs, and beam–column joints. The results reveal significant spatial variability in compressive strength and pulse velocity values, indicating non-uniform thermal damage and internal cracking, with several load-critical elements exhibiting poor to severely degraded concrete quality. The study demonstrates that NDT methods provide an effective preliminary tool for identifying critically damaged zones but are insufficient alone for complete structural safety evaluation. Based on the findings, recommendations are proposed for detailed assessment and destructive testing to support informed decisions regarding repair, strengthening, or demolition of fire-damaged RCC buildings.